Application of AOO and catalytic ozonation process in the treatment of coking wastewater in cold regions - ZHAO Guohua; LIU Wei; LI Jingxu (Gongye shui chuli)
Taking a coking wastewater treatment plant in Inner Mongolia as a case study, this paper provided a detailed introduction to the local climate characteristics, project construction scale, inlet and outlet water quality, adopted process flow, and main design points of each unit determined by fully considering the impact of low temperatures in winter. The relevant designs of equipment insulation, pipeline venting and insulation, and structural insulation were summarized. The actual operating results showed that the AOO and catalytic ozonation process used for treating coking wastewater in cold regions had good and stable operating effects. Even under the influence of low temperatures in winter, the various pollutant indicators in the enhanced deep treatment effluent could stably reach the direct discharge limit specified in Table 2 of the “Emission Standard of Pollutants for Coking Chemical Industry”(GB 16171-2012), and the operating cost was within an acceptable range.